2018
DOI: 10.1177/0194599817751072
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid Carcinoma: A 23‐Year Experience with Emphasis on Low‐Grade Tumors with Close/Positive Margins

Abstract: Objective Describe outcomes for mucoepidermoid carcinoma by histologic grade and evaluate outcomes for patients with low-grade tumors with close/positive margins after initial surgical resection. Study Design Cohort study. Setting Kaiser Permanente Southern California Medical Group from 1993 to 2016. Subjects and Methods Retrospective review of 154 patients with major and minor salivary gland mucoepidermoid carcinoma of the head and neck. Disease-specific and recurrence-free survival were stratified by tumor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…Similarly, Cho et al [7] reported on the impact of close margins after resection of parotid malignancy in a larger multivariable analysis but did not specifically investigate the effect of radiotherapy on this patient population. Finally, Spellman and Calzada [22] recently analyzed 154 patients with MEC of the head and neck and also found that further treatment of patients with close margins, either revision surgery or radiotherapy, did not significantly impact survival outcomes. These authors, however, included a more heterogenous group of tumors, from sites other than parotid as well as advanced-stage disease, and grouped both close and positive margins for analysis, without identifying radial margin distance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cho et al [7] reported on the impact of close margins after resection of parotid malignancy in a larger multivariable analysis but did not specifically investigate the effect of radiotherapy on this patient population. Finally, Spellman and Calzada [22] recently analyzed 154 patients with MEC of the head and neck and also found that further treatment of patients with close margins, either revision surgery or radiotherapy, did not significantly impact survival outcomes. These authors, however, included a more heterogenous group of tumors, from sites other than parotid as well as advanced-stage disease, and grouped both close and positive margins for analysis, without identifying radial margin distance.…”
Section: Discussionmentioning
confidence: 99%
“…Mucoepidermoid carcinoma is the most common type of malignancies originating from major salivary gland. Despite of its relatively low incidence, the clinical behavior of MEC differs tremendously, from slow growing indolent tumor with a generally good prognosis to aggressive tumor accompanied with distant metastasis and causing high mortality rate 7, 17, 18. Treatment strategies of MEC evolve as time goes by.…”
Section: Discussionmentioning
confidence: 99%
“…Jegadeesh et al reported that in parotid MEC, no adjuvant radiation and older age at diagnosis were associated with increased risk of local regional recurrence, underlining the essentiality of postoperative radiotherapy 20. Spellmen et al, on the other hand, argued that in low-grade MEC, additional treatment had no impact on survival or recurrence 17. Inconsistencies like this arise widely among existent researches, challenging the management of MaSG-MEC.…”
Section: Discussionmentioning
confidence: 99%
“…15 Histologic grades were categorized according to the classification for head and neck salivary gland cancers established by the World Health Organization. 2 16 Surgical margins from pathology reports were classified as R0 (negative margin), R1 (microscopically positive margin), or R2 (macroscopically positive margin). R0 was further subclassified into clear margins (>1 mm) or close margins (≤1 mm).…”
Section: Meaningmentioning
confidence: 99%